High-throughput methods of regulatory element discovery. (December 2006) - Hudson, Michael E.; Snyder, Michael
With the number of organisms whose genomes have been sequenced, a vast amount of information concerning the genetic structure of an organism's genome has been collected. However, effective experiment means to study how this information is accessed have only recently been developed. In this review, three basic methods for identifying regions of protein-DNA interaction will be introduced. The first two, chromatin immunoprecipitation (ChIP)-chip and ChIP-PET (for paired-end ditag), rely on the enrichment provided by chromosomal immunoprecipitation to interrogate the genomic sequence for the interaction sites of a protein of interest. In contrast, protein microarrays allow the identification of DNA binding protein that interacts with a DNA sequence of interest. These complementary methods of exploring protein-DNA interactions will increase our fundamental knowledge of how the information contained within the genome sequence is accessed and processed.